Dcdd Donors Are Not Dead - Joffe, Ari (The Hastings Center report, 2018)
According to international scientific medical consensus, death is a biological, unidirectional, ontological state of an organism, the event that separates the process of dying from the process of disintegration. Death is not merely a social contrivance or a normative concept; it is a scientific reality. Using this paradigm, the international consensus is that, regardless of context, death is operationally defined as “the permanent loss of the capacity for consciousness and all brainstem function. This may result from permanent cessation of circulation or catastrophic brain injury. In the context of death determination, ‘permanent’ refers to loss of function that cannot resume spontaneously and will not be restored through intervention.” The word “permanent” replaces “irreversible” (used in the United States’ 1980 Uniform Declaration of Death Act) in this new definition, arguably invented to allow donation after circulatory determination of death (DCDD) while still complying with the dead donor rule. I will show that this invention fails, for at least four reasons.